2021
DOI: 10.35721/jakiyah.v6i1.63
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Intensitas Penggunaan Game Online Dengan Kualitas Tidur Pada Remaja

Abstract: Latar Belakang: Penggunaan game online yang tinggi membuat individu mengalami kecanduan yang memberikan berbagai dampak terhadap perilaku individu. Salah satu dampak dari penggunaan game online adalah berkurangnya waktu istirahat yang mana pengguna game online bermain tanpa mengenal waktu dan hal tersebut sangat mempegaruhi kualitas tidur. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan intensitas penggunaan game online dengan kualitas tidur pada remaja di SMK N 01 Pleret Bantul Yogyakarta.&#x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
1
0
0
2
Order By: Relevance
“…Based on the results of measuring the social media addiction variable, it was found that 61.94% of respondents were in the high category. This result is in line with other research, which also shows that more than half of the respondents in adolescents (high school students), and as many as 43 people (50.6%) are in the high category of social media addiction (Ariani, Elita & Zulfitri, 2009). Most adolescents think that the more active they are on social media, the more relaxed and social they will be considered.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the results of measuring the social media addiction variable, it was found that 61.94% of respondents were in the high category. This result is in line with other research, which also shows that more than half of the respondents in adolescents (high school students), and as many as 43 people (50.6%) are in the high category of social media addiction (Ariani, Elita & Zulfitri, 2009). Most adolescents think that the more active they are on social media, the more relaxed and social they will be considered.…”
Section: Discussionsupporting
confidence: 91%
“…Physical Therapy Journal of Indonesia 2023; 4(2): 173-176; DOI: 10.51559/ptji.v4i2.121 of sleep of adolescents, found that the causes of adolescents playing online games excessively are caused by boring routines and a home atmosphere that is far from comfortable. 16 The same thing was also found in Yustina's research (2021) concerning the relationship between online game addiction and student sleep quality. It found that adolescents are more prone to experiencing poor sleep quality due to accessing the internet too often to play and forgetting time to rest at night, which will impact health.…”
Section: Original Articlesupporting
confidence: 60%
“…An increased likelihood of musculoskeletal symptoms was linked to weekday online gaming for more than five hours a day in combination with escape motives (OR 2.494, 95% CI 1.598 -3.892) (Hellström et al, 2015). Nofianti (2018) showed that adolescents who played games online with high intensity had poor sleep quality, an issue affecting 101 respondents (85.1%). Another study showed that children who played online games for longer than six hours had the worst sleep quality (75%) (Ahmed et al, 2022;Jeong et al, 2021).…”
Section: Discussionmentioning
confidence: 99%